Social connections and smallholder vegetable farmers’ collaborative marketing strategy: The case of the small farmers association of Quirogpang in Davao City, the Philippines - Montiflor, M.; dela Cerna, A.; Lamban, R.; Bacus, R.; Concepcion, S.; Batt, Peter; Murray-Prior, Roy (International Society of Horticultural Science, 2011)
In the Philippines, vegetable farmers generally have only small land holdings. Because of this, plus an apparent lack of financial capital, it is difficult for smallholder farmers to meet the large volume demands imposed by institutional buyers and wholesalers. The small volume and the large variation in quality puts smallholder farmers at a significant disadvantage when it comes to arranging transport and marketing. However, smallholder farmers can engage in collaborative cluster farming in order to meet the demands of the market and to bolster production volume. In the cluster, the farmers carry out production planning and marketing activities collectively. Utilizing the case study method and the 8-step clustering approach formulated by the Catholic Relief Services, this paper will present key success factors and several challenges faced by the Small Farmers Association of Quirogpang (SFAQ) in Marilog, Davao City, Philippines. At the same time, it will identify important institutional supports and strategies that may enhance the success of this and other clusters. The paper highlights key success factors such as the social connections shared by the cluster members and leadership. In this case, these commonalities exist because it is an area-based cluster which includes neighbours and relatives who all practice one religion and speak the same language or dialect.